Gender and equestrian sport : riding around the world - Knijnik, Jorge; Adelman, Miriam (Springer Netherlands, 2013)
This volume brings together studies from various disciplines of the social sciences and humanities (Anthropology, Sociology, Cultural Studies, History and Literary theory) that examine the equestrian world as a historically gendered and highly dynamic field of contemporary sport and culture.  From elite international dressage and jumping, polo and the turf, to the rodeo world of the Americas and popular forms of equestrian sport and culture, we are introduced to a range of issues  as they unfold at local and global, national and international levels. Students and scholars of gender, culture and sport  will find much of interest in this original look at contemporary issues such as "engendered" (women's and men's) dentities/subjectivities of equestrians, representations of girls, horses and the world of adventure in juvenile fiction;  the current "feminization" of particular equestrian activities (and where boys and men stand in relation to this);  how broad forms of social inequality and stratification play themselves out within gendered equestrian contexts; men and women and their relation to horses within the framework of current discussions on the relation of animals to humans (which may  include not only love and care, but also exploitation and violence), among others.  Singular contributions that incorporate a wide variety of classic and contemporary theoretical perspectives and empirical methodologies show how   horse cultures around the globe contribute to historical and current constructions of embodied "femininities" and "masculinities", reflecting a world that has been moving "beyond the binaries" while continuing to be enmeshed in their persistent and contradictory legacy.  The final chapter makes a brave attempt at synthesizing individual chapters and moving forward from the evidences they provide,  to suggest a compelling agenda for future research.